Toward a Sports-Based Behavior Contract Model for ADHD Management in Inclusive Schools: Evidence from a Systematic Literature Review - Rahmad Firmansyah; Putri Lagenda Wulandari; Safrina Safrina; Indah Musaqina; Artha Efanjelica Hutagalung (IGI Active Living and Health Insight, 2026)
Purpose of the study: This systematic literature review aimed to synthesize the existing evidence on the effectiveness of integrating behavior contracts and adaptive physical activity as complementary interventions for managing Attention Deficit Hyperactivity Disorder (ADHD) in inclusive school settings. The review also sought to identify research gaps and establish a conceptual foundation for developing a sports-based behavior contract model. Materials and methods: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was retrieved from Google Scholar, Garuda, and the Directory of Open Access Journals (DOAJ) using predefined keywords related to behavior contracts, adaptive physical activity, ADHD, hyperactivity, and inclusive education. Studies published between 2016 and 2026 in English or Indonesian were screened based on predefined inclusion and exclusion criteria. Following the identification, screening, eligibility, and quality assessment processes, thirteen studies were included in the thematic synthesis. Results: The findings demonstrate that behavior contracts consistently enhance students' behavioral commitment, self-regulation, and adherence to targeted behaviors through structured reinforcement mechanisms. Meanwhile, adaptive physical activities—including swimming, martial arts, gymnastics, and motor-based games—effectively reduce hyperactivity, improve attentional control, and promote executive functioning among children with ADHD. However, no reviewed study empirically integrated these two evidence-based approaches into a unified intervention framework. This gap highlights the potential of combining structured physical activity with behavior contracts to simultaneously strengthen behavioral regulation and channel excess motor activity within inclusive educational environments. Conclusions: Current evidence supports the complementary effectiveness of behavior contracts and adaptive physical activity for ADHD intervention; nevertheless, their integration remains underexplored. The proposed sports-based behavior contract model represents a promising conceptual framework that warrants future empirical validation through experimental and longitudinal studies in inclusive schools.